The Implementation of Qiraat As-Sab'ah Learning at Nurul Islam Elementary School, Sumbawa - Usman, Taufiqurrahman (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
Al-Qur'an learning plays a vital role in shaping the religious competence of students from an early age. One form of deepening Al-Qur'an recitation is qiraat as-sab'ah, which reflects the diversity of mutawatir recitations. This study aims to describe the implementation of qiraat as-sab'ah learning at Nurul Islam Elementary School in Sumbawa, including planning, implementation, and evaluation of learning. This study uses a qualitative approach with field research. Data collection techniques were carried out through observation, interviews, and documentation. The results show that the teaching of qiraat as-sab'ah at Nurul Islam Sumbawa Elementary School is carried out in stages, emphasizing mastery of qiraat hafs before introducing other variations of qiraat. The talaqqi and musyafahah methods were the main methods, while evaluation was carried out through oral tests and reading practice. The implementation of this learning contributed positively to improving the quality of the students' Al-Qur'an reading.